293 Futbol club Barcelona ACL injury epidemiology. (3rd March 2020) - Leyes, Javier Yanguas; Meca, Sandra Mechó; Serrallach, Xavier Alomar; Grivé, Ricard Pruna; Rodas, Gil
Abstract : Background: Rupture of the anterior cruciate ligament (ACL) is one of the most disabling, potentially career-threatening, knee injuries in professional football players, and requires surgical reconstruction to recover the pre-injury competitive level. Complete ACL rupture results in highly variable time-loss, but often requires 6 to 9 months of rehabilitation in professional players. The incidence of ACL rupture is 0.07 per 1000 in males, and may be 2–4 times higher in females. Objective: To determine the incidence of ACL injury in football teams at Futbol Club Barcelona (FCB), including male and female players, and professional and youth categories, and to assess exposure data (match and training) during 8 consecutive seasons (2010–2011 to 2017–2018). Design: Retrospective epidemiological study. Patients (or Participants): Total sample size was 2, 872 players (2, 304 males, and 568 females) divided into 4 categories: professional male (>19 years old, n=512), youth boys (<19 years old, n=1, 792), professional female (>18 years old, n=168), and youth girls (<18 years old, n=400). Data on exposure time were collected by the technical staff of each team, and medical diagnosis and follow-up were conducted by members of FCB medical staff. Results: Thirty-four injuries were registered: 17 in males (9 in professional, 8 in youth) and 17 in females (6 in professionals, 11 in youth). General ACL injury incidence was 4.5 times higher in females (0.18 vs 0.04) than in males (2.7 and 5.7 times higher in professionals and youth players, respectively). Injury incidence was higher in matches than in training (3.4 and 17 times higher in males (0.11 vs 0.03) and females (0.86 vs 0.05), respectively). Non-contact injuries accounted for 88% of injuries in males, and almost all injuries in females (94%). Lateral meniscus injuries were especially common in females (65%), whereas isolated ACL tears were more common in males (68%). Conclusions: The incidence of ACL injury was 4.5 times higher in female football, higher in matches than in trainings.